Biliary cast syndrome after liver transplantation: A cholangiographic evolution study. Issue 5 (10th November 2020) - Lemmers, Arnaud; Pezzullo, Martina; Hadefi, Alia; Dept, Séverine; Germanova, Desislava; Gustot, Thierry; Degré, Delphine; Boon, Nathalie; Moreno, Christophe; Blero, Daniel; Arvanitakis, Marianna; Delhaye, Myriam; et al.
Abstract: Background and Aim: The aim of this study is to describe the cholangiographic features and endoscopic management of biliary cast syndrome (BCS), a rare specific ischemic cholangiopathy following liver transplantation. Methods: Patients with biliary complications were identified from prospectively collected database records of patients who underwent liver transplantation at the Erasme Hospital from January 2005 to December 2014. After excluding patients with hepatico‐jejunostomy or no suspicion of stricture, cholangiograms obtained during endoscopic retrograde cholangiopancreatography (ERCP) and magnetic resonance imaging were systematically reviewed. Biliary complications were categorized as anastomotic (AS) and non‐AS strictures, and patients with BCS were identified. Clinical, radiological, and endoscopic data were reviewed. Results: Out of 311 liver transplantations, 14 cases were identified with BCS (4.5%) and treated with ERCP. Intraductal hyperintense signal on T1‐weighted magnetic resonance and a "duct‐in‐a‐duct" image were the most frequent features of BCS on magnetic resonance imaging. On initial ERCP, 57% of patients had no stricture. Complete cast extraction was achieved in 12/14, and one of these had cast recurrence. On follow‐up, 85% of the patients developed biliary strictures that were treated with multiple plastic stents reaching 60% complete stricture resolution, but 40% of them had recurrence. After a median follow‐up of 58 months, BCS patients had lower overall and graft survival (42.9% and 42.9%) compared with non‐AS (68.8% and 56.3%) and AS (83.3% and 80.6%), respectively. Conclusions: Particular magnetic resonance‐cholangiographic and ERCP‐cholangiographic features of BCS have been identified. Outcomes for BCS are characterized by high complete cast extraction rates, high incidence of secondary strictures, and poorer prognosis.